Integrating palaeocaves into palaeolandscapes: An analysis of cave levels and karstification history across the Gauteng Malmani dolomite, South Africa. (15th September 2019) - Herries, Andy I.R.; Adams, Justin W.; Joannes-Boyau, Renaud; Armstrong, Brian; Baker, Stephanie; F. Blackwood, Alex; Boschian, Giovanni; V. Caruana, Matt; Penzo-Kajewski, Paul; Murszewski, Ashleigh; S. Rovinsky, Douglass
Abstract: The Drimolen Palaeocave System in the 'Fossil Hominid Sites of South Africa' UNESCO World Heritage Site is well known for numerous remains of early hominins such as Paranthropus robustus and early Homo . These hominin fossils, along with bone tools and notably diverse accumulation of non-hominin primates and fauna, have all been excavated from the 'Main Quarry' area of the site where extensive lime-mining took place. Here we report the first radiometric age of 1.712 ± 0.269 Ma for hominin bearing deposits associated with the DNH7 Paranthropus robustus cranium in the Main Quarry area of the site, which is consistent with recent biochronological estimates. This age is similar to recent estimates for Swartkrans Member 1 Hanging Remnant (somewhere between 2.3 and 1.8 Ma) which also contains Paranthropus and early Homo . Simultaneously, we integrate the newly radiometrically dated Main Quarry deposits with a new fossil deposit, the Drimolen Makondo, discovered in 2013, that is situated some 50 m up the hill to the west from the Main Quarry. It has experienced only limited disturbance from mining but much more extensive erosion. Preliminary excavations and analysis have revealed that the Makondo infill is older than the Main Quarry, dating to 2.706 ± 0.428 Ma. Its greater age is confirmed by biochronology. The Makondo thus overlap with the suggested end of deposition of Australopithecus bearing Sterkfontein deposits, although it is yet to yield any hominin remains. These new dates for the two Drimolen Palaeocave System deposits indicates that, contrary to prior age estimates, the Drimolen site as a whole records the critical hominin and faunal turnover in South African palaeocommunities that occurred around 2.3–1.7 Ma. Finally, as the Drimolen Makondo represents a rare example of a pre-2 Ma fossil bearing deposit in the Gauteng exposures of the Malmani dolomite, we also integrate our results into the greater South African record of palaeodeposit formation (most of which occur between ∼2.0 and 1.0 Ma). An analysis of the age of palaeocave infillings across the Malmani dolomite suggests that, as is classically the case with karst, the height within the dolomite is broadly correlated to their age, although with some notable exceptions that are likely related to localised geological features. Our analysis also indicates that most caves have undergone some form of secondary karstification related to a younger phase of cave formation, contrasting with models that suggest the cavities all formed at the same time and that infill is related to erosion and the opening up of cave passages. As such, the reason that few pre-2 Ma deposits have been identified in the Gauteng exposures of the Malmani dolomite is probably because these older caves have been eroded away. Identifying such early caves is critical in understanding whether earlier hominins may have once existed in South Africa or if erosion of older deposits (or an absence of speleogenesis at this time) has made such early periods absent from the geological record. Highlights: The first radiometric age (∼ <2.0->1.4Ma) for the DNH7 Paranthropus robustus cranium. Describes a new older fossil deposit (∼<3.1->2.3 Ma) from Drimolen. An age for the first documented overlap of two species of Dinofelis in S. Africa. A new model for cave formation in the Cradle of Humankind (S. Africa). A model for understanding geological bias in the S. African hominin record.